2020
DOI: 10.1186/s12868-020-00590-4
|View full text |Cite
|
Sign up to set email alerts
|

Distributed causality in resting-state network connectivity in the acute and remitting phases of RRMS

Abstract: Background Although previous studies have shown that intra-network abnormalities in brain functional networks are correlated with clinical/cognitive impairment in multiple sclerosis (MS), there is little information regarding the pattern of causal interactions among cognition-related resting-state networks (RSNs) in different disease stages of relapsing–remitting MS (RRMS) patients. We hypothesized that abnormalities of causal interactions among RSNs occurred in RRMS patients in the acute and remitting phases.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Most studies have performed RS fMRI studies during remission, given concerns of relapse-driven inflammation influencing signal stability, however, some relapse studies have been done. ( Wu et al, 2020 ) Findings below explore disability and cognition, but it should be noted similar results have also been found for other symptoms such as fatigue ( Manjaly et al, 2019 ) and social cognition. ( Chalah and Ayache, 2020 ).…”
Section: From Segregation To Integrated Functional Network: the Role ...mentioning
confidence: 60%
See 1 more Smart Citation
“…Most studies have performed RS fMRI studies during remission, given concerns of relapse-driven inflammation influencing signal stability, however, some relapse studies have been done. ( Wu et al, 2020 ) Findings below explore disability and cognition, but it should be noted similar results have also been found for other symptoms such as fatigue ( Manjaly et al, 2019 ) and social cognition. ( Chalah and Ayache, 2020 ).…”
Section: From Segregation To Integrated Functional Network: the Role ...mentioning
confidence: 60%
“…Effects were mostly seen in the DMN Meijer et al, 2020 133 people with MS 48 HC In people with MS and a long disease duration, structural connectivity loss was worst in long-distance connections, and was related to a more abnormal RS FC. Both functional and structural RS FC changes related to worse CI Riccitelli et al, 2020 37 people with benign MS 50 HC Increased RS FC in fronto-temporo-parietal regions was seen in MS, but was not included as a predictor of worse CI in a multivariate model Wu et al, 2020 17 people with MS and relapse 24 people with MS in remission 23 HC People with MS undergoing a relapse had more severe RS FC changes, which were related to worse PASAT scores compared to remitting people with MS and HC Tommasin et al, 2020 119 people with MS 42 HC Within-network RS FC was higher in MS for DMN, FPN and ECN and were related to less severe disability and PASAT impairment. Lower between-network and whole-brain RS FC was also lower, but related to worse impairments Bizzo et al, 2021 28 people with MS 28 HC Better cognitive reserve was related lower RS FC of the dorsal anterior insula with cuneus and parieto-occipital areas Jandric et al, 2021 55 cognitively impaired people with MS 47 cognitively preserved people with MS 27 HC Decreased DMN but increased FPN FC was found in cognitively impaired vs preserved people with MS, combined with altered cerebral blood flow and structural disconnection Dekker et al, 2021 295 people with MS 96 HC Event-based model showed early involvement of DMN centrality changes related to disability and cognitive progression Marchesi et al, 2021 116 people with MS 65 HC RS FC of working memory, ECN, salience network and DMN related to worse Wisconsin card sorting outcomes Pasqua et al, 2021 119 people with MS 42 HC Increased cerebellar RS FC related to lower cognitive and physical disability Soares et al, 2021 21 people with MS 17 HC Lower RS FC was related to white matter lesion load and information processing Buyukturkoglu et al, 2021 181 people with early MS Machine learning approaches were able to differentiate low- and high-performing S...…”
Section: From Segregation To Integrated Functional Network: the Role ...mentioning
confidence: 99%
“…For example, the significantly decreased FA and increased MD avulses found in ACR regions may correspond to the anterior functions of the default mode network (DMN). In addition, the NAWM changes in SCC and PTR regions may be related to the posterior part of DMN ( Bonavita et al, 2011 ; Wu et al, 2020 ). Moreover, the significant MD and RD value changes in RRSM patients may be relevant to the DMN and dorsal attention networks ( Huang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Seven out of twenty studies looking at fatigue and fMRI used a task-based approach [35, 115, 122124, 129, 149], and 13/20 used rs-fMRI [110, 111, 121, 125, 126, 134, 138, 141144, 148, 151] (Table 1). Only 3/20 studies [121, 142, 143] did not observe functional changes in fatigued RRMS patients, while seventeen out of twenty studies reported associations with fatigue for one or more regions (Fig 2 and Table 4).…”
Section: Resultsmentioning
confidence: 99%